The Effect of Online Dialogic Parent-child Book Reading on Preverbal and Listening Skills of Deaf Children Under Three Years Old - Sima Razmi; Guita Movallali; Talieh Zarifian; Sina Ahmadi (Journal of Rehabilitation, 2023)
Objective Deafness is one of the most complex sensory disorders that leads to a major decline in auditory (listening) and preverbal skills. Research shows that reading books has provided patterns of communication and preverbal skills to deaf children. This study was conducted to investigate the effect of online dialogic parent-child book reading on the preverbal and listening skills of deaf children under three years old. Materials & Methods This research was a one-group quasi-experimental study with a pre-test-post-test design. The study sample comprised 10 hearing parents with their deaf children under 3 years old who were members of the Deaf Family Association of Iran and the Deaf Center of Iran. First, the parents and their qualified children were purposefully identified (based on inclusion criteria). Then, from all the people who met the study criteria, the people who declared their readiness to participate were selected as study samples. Before starting the online dialogic parent-child book reading program, the preverbal skills test (pointing, joint attention, imitation, and take turns) and listening skills (little ears) were administered as a pre-test. Online reading sessions were held for 20 sessions, three days a week. Parents went online at a specific time (10 AM on Saturdays, Mondays, and Wednesdays). Each day a book with pictures and story-related content, book descriptions, questions, and more was posted in the WhatsApp group. After the online dialogic parent-child book reading program, the test of preverbal and listening skills (little ears) was performed as a post-test for the sample group. The paired t-test was used to analyze the obtained data. Results The results of this study showed that the online dialogic parent-child book reading program caused a significant increase (P<0.005) in the post-test preverbal skills test score (imitation, joint attention, pointing and take turns) and listening skills (P<0.005) compared with the pre-test score of the sample group. Conclusion Dialogic parent-child book reading is one of the parent-centered programs that is benefecial for deaf toddlers. The results showed the applicability of dialogic parent-child book reading in improving the listening and preverbal skills of deaf children.